INTRAOCULAR CORRECTION OF PRESBYOPIA BY MONOVISION IN PATIENTS WITH CATARACT AND CORNEAL ASTIGMATISM - E. I. Belikova (Oftalʹmologiâ)
Purpose: To evaluate the results of intraocular correction of presbyopia by monovision in patients with cataract and primary corneal astigmatism and conduct a comparative analysis of these outcomes with the results of binocular multifocal IOLs implantation. Patients and methods. There were 21 patients with bilateral cataract surgery performed using toric monofocal intraocular lenses (monovision group) in the study. The indications for the operation were: 1) primary corneal astigmatism ≥ 1.0D in patients with cataract, 2) inability to conduct excimer laser correction. Reduction of spectacle dependence by monovision was discussed during preoperative conversation. The age of patients range from 32 to 65 years. Target refraction: Emetronopia on the dominant eye (DG) and myopia at 1.0–2.0 D in the non-dominant eye (NDG). Evaluation included measurement of uncorrected visual acuity, refraction, stereopsis, contrast sensitivity and patient satisfaction. The results were compared with the outcomes of binocular multifocal Iols implantation in 22 patients (44 eyes). Results. The spherical component decreased from 3.39±2.63D to 0.34±0.24D, cylinder decreased from 3.05±1.47D to 0.44±0,35D (P <0.01) in the monovision group three months after surgery . The deviation from target refraction was 0.30±0.35D. The mean difference between postoperative refraction on the two eyes was 1.92±0.57D. Postoperative corrected visual acuity significantly exceeded preoperative parameters. In 18 patients (88%) the stereoscopic visual acuity did not exceed 60 seconds and corresponded to the age norm, in 3 patients (12%) it was at the level of 80–100 arc seconds. In patients with multifocal IOLs, the stereovision values were identical (Ferrer-Blasco T. et al, 2008). Conclusion. The monovision is an effective method of reducing dependence on additional correction in patients with cataract and corneal astigmatism. Refractive outcomes, binocular visual acuity, predictability and stability are comparable with the results after multifocal IOLs implantation.